Donor-substituted heptaazaphenalene as a nonlinear optically active molecule with multiple charge-transfer transitions - Traber, Boris; Oeser, Thomas; Gleiter, Rolf; Goebel, Mark; Wortmann, Rüdiger (European journal of organic chemistry, 2004)
The synthesis of a novel nonlinear optical (NLO) chromophore with threefold symmetry − 2,5,8-tris(diethylamino)-1,3,4,6,7,9,9b-heptaazaphenalene (4) − is reported. Compound 4 was synthesized from 2,5,8-trichloro-1,3,4,6,7,9,9b-heptaazaphenalene (3) through a nucleophilic aromatic substitution, its structural assignment was confirmed by X-ray investigations, and its second-order polarisability (β) was determined by hyper Rayleigh scattering (HRS). Compound 4 shows a very high absorbance coefficient in the UV and a remarkably large β value despite its short-wavelength absorption. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2004)